2021
DOI: 10.1371/journal.ppat.1009644
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the unfolded protein response: A pharmacological strategy against coronavirus infection

Abstract: Coronavirus infection induces the unfolded protein response (UPR), a cellular signalling pathway composed of three branches, triggered by unfolded proteins in the endoplasmic reticulum (ER) due to high ER load. We have used RNA sequencing and ribosome profiling to investigate holistically the transcriptional and translational response to cellular infection by murine hepatitis virus (MHV), often used as a model for the Betacoronavirus genus to which the recently emerged SARS-CoV-2 also belongs. We found the UPR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 121 publications
(209 reference statements)
5
73
0
Order By: Relevance
“…The contribution of ORF8 to ER stress was additionally confirmed by studying two genotypes of SARS-CoV-2, namely ORF8L and ORF8S, which carry a Leucine or a Serine at position 84 and were identified during the early stages of the pandemic in China. Despite lacking the aggregation motif found in SARS-CoV (270), both ORF8L and ORF8S are able to trigger the activation of ATF6 and IRE1 (71) and PERK (271). SARS-CoV-2 ORF8 is encoded by a hypervariable gene and several different polymorphisms have already been identified, as reported by a recent review (73).…”
Section: The Interaction Of Orf3a With the Apoptosis And Autophagy Pathwaysmentioning
confidence: 91%
“…The contribution of ORF8 to ER stress was additionally confirmed by studying two genotypes of SARS-CoV-2, namely ORF8L and ORF8S, which carry a Leucine or a Serine at position 84 and were identified during the early stages of the pandemic in China. Despite lacking the aggregation motif found in SARS-CoV (270), both ORF8L and ORF8S are able to trigger the activation of ATF6 and IRE1 (71) and PERK (271). SARS-CoV-2 ORF8 is encoded by a hypervariable gene and several different polymorphisms have already been identified, as reported by a recent review (73).…”
Section: The Interaction Of Orf3a With the Apoptosis And Autophagy Pathwaysmentioning
confidence: 91%
“…All three branches of the UPR were induced in MHV, SARS-CoV-2, PEDV, and TGEV infected cells (Versteeg et al, 2007;Xue et al, 2018;Chen et al, 2021;Echavarria-Consuegra et al, 2021). Pharmacological inhibition of the UPR greatly regulated coronavirus replication, revealing the importance of this pathway for successful coronavirus replication.…”
Section: Regulation Of Coronavirus Replication By Unfolded Protein Responsementioning
confidence: 98%
“…Interestingly, the accessory protein 3a of SARS-CoV, a small multipass transmembrane protein, also activates the ATF4 and Chop promoter activities and thus may potentially also activate the PERK branch of UPR (Minakshi et al, 2009). MHV infection leads to activation of PERK-eIF2α-ATF4 branch (Figure 2; Echavarria-Consuegra et al, 2021).…”
Section: The Perk Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…the inositol requiring enzyme 1 (IRE1), the double stranded RNAactivated PK-like ER kinase (PERK), and the activating transcription factor 6 (ATF6) (Wang et al, 2014b). Although UPR activation is observed during SARS-CoV-2 infection (Echavarría-Consuegra et al, 2021), chemical activation of UPR by thapsigargin has been shown to inhibit coronavirus replication, including SARS-CoV-2 (Shaban et al, 2021). Furthermore, modulating the PERK-eIF2α pathway can inhibit the replication of the transmissible gastroenteritis porcine coronavirus (Xue et al, 2018).…”
Section: Streptococcus Pneumoniae -The Leading Cause Of Bacterial Pneumonia Worldwide -Andmentioning
confidence: 99%